The Gait as Political Choreography : Political School Ceremonies for the Consolidation of the Nation-State in Germany and Japan (1873-1945) - Kobayashi, Ami (2024)
This book explores the upright gait in the school context and the collective gait of adolescents as a political choreography in Germany and Japan that contributed to the consolidation of the nation-state. In shedding light on the transnational character of the marching ceremony, this book reveals how the nationalization of school-attending youths deeply relied on emotionally-charged, collective bodily experiences.